PENERAPAN SISTEM OTOMASI DALAM PEMBERIAN PAKAN IKAN LELE GUNA MENGEFISIENSI WAKTU - Sanam, Sanam; Azpah, Inda Aidatul; Bohari, Bohari; Abdillah, Hamid; Putra, Ananda Yutho Wibisono (Politeknik Negeri Cilacap, 2024)
Catfish is a cultivated fishery commodity that has quite large business opportunities to be developed to fulfill community nutrition. Feeding in catfish farming is very important and is one of the things that really needs to be considered. Feeding must be planned so that catfish can grow optimally. Unscheduled feeding results in increased cannibalism among catfish. The use of an automation system must be implemented in order to make it easier and more efficient in feeding catfish. The research method used in writing this scientific work is by using literature study. The purpose of this writing is to find out and implement an automation system for feeding catfish to make it easier and more efficient in feeding catfish. The results obtained from this automatic tool can make it easier for humans to operate, so that it no longer needs to be powered manually. Just automatically use the feeder. In conclusion, the implementation of an automatic system using IoT and Arduino Uno has been proven to be able to streamline catfish feeding times.